SEXUAL ASSAULT, FORENSIC INVESTIGATION, AND LEGAL SYSTEM IN PAKISTAN: A REVIEW - RAZA, MS; AHAD, A; NAWAZ, R; AHMAD, M; HASSAN, JU; MEHMOOD, U (Biological and Clinical Sciences Research Journal, 2023)
Sexual assaults are horrific crimes and major human rights violations everywhere, particularly against women and children. According to statistical surveys around the globe, the occurrences of sexual assaults are more common in developed countries. According to different survey reports published in The Nation, almost 11 cases are reported every 24 hours in Pakistan. Besides this high occurrence rate of rape cases, many cases go unreported. Conviction rates are surprisingly as low as 0.5% due to multiple factors like the unfamiliarity of victims with the legal procedures and basic human rights, the social pressure created by the families of victims, time-consuming and challenging legal processes, worry about retaliation from the attacker etc. With the prevalence of modern scientific technologies and trends in the World, modern and improved technologies and techniques like DNA testing and DNA profiling are being used in Pakistan also, even with the limited availability of full-fledged forensic labs. The need of the hour is to spread awareness and to enhance the literacy rate because more than 60 million people lack knowledge about basic human rights and the legal procedures regarding assault cases that they must follow in case of any unfortunate happenings.